Interconnectedness of Economic Variables: Insights from Pakistan’s Endogenous Growth Model - Khan, Muhammad Zia Ullah; Rehman, Fatima (Journal of Business and Economic Options, 2021)
The study delves into the intricate relationship between money, monetization, and economic growth in the context of Pakistan, seeking to unravel the dynamics that underpin the country's economic performance. With a focus on the endogenous growth theory, the research aims to empirically test the Standard Growth Model, which serves as the theoretical framework for understanding the interplay between key variables. At the heart of the analysis lies the examination of the relationship between various factors—such as inflation, income distribution, investment, stock market performance, and money supply and gross domestic product per capita, which serves as a proxy for economic growth. Through the use of the auto regressive distributed lag Approach, the study employs co-integration analysis to ascertain the existence of a long-term equilibrium relationship among these variables. The findings of the co-integration analysis reveal compelling evidence of a long-term equilibrium relationship between the variables under investigation. This suggests that changes in one variable have a lasting impact on the others, underscoring the interconnectedness of economic phenomena in Pakistan. Furthermore, the application of the Error Correction Model sheds light on the short-term dynamics between money supply and economic growth, with the results indicating a negative and significant relationship. By uncovering these empirical relationships, the study contributes valuable insights to the understanding of Pakistan's economic dynamics and provides a basis for informed policymaking. It highlights the importance of considering the multifaceted interactions between monetary variables and economic performance, emphasizing the need for policies that promote stability, investment, and sustainable growth. Ultimately, the research serves as a valuable resource for policymakers, economists, and stakeholders seeking to navigate the complexities of Pakistan's economic landscape and foster robust and inclusive growth.